The Legal Protection for Child Perpetrators and Victims of Revenge Porn in Indonesia - Rumondor, Jenaya Adra; Jennifer, Graceyana; Desintha, Pande Ketut Natalia (Faculty of Law Universitas Negeri Semarang, 2022)
The development of the digital world brings so many benefits to human life, which includes all levels of people, from children to adults. For children, the digital world and social media will certainly support a more advanced and developing life. However, this progress also presents various potentials and challenges that are not in line with the fulfillment of children's growth and development rights. This is related to the threat of children's rights in criminal acts based on social media, both as perpetrators and as victims of the crime itself. One of these crimes is online gender-based violence that is rife in the form of cyberporn with revenge porn modus operandi, which is a crime by spreading vulgar content without the consent of the person in the content to take revenge. The research method used is a descriptive-analytical research method with a normative legal approach, where the author uses secondary data and a statutory approach to draw deductive conclusions. Therefore, the government needs to actively implement legal protection to protect the rights of children as victims and perpetrators. Such legal protection should be carried out in a preventative manner with the Virtual Police mechanism and the role of the Stakeholders, and repressively by carrying out the judiciary, instilling the concept of restorative justice in its implementation, both in the application of diversion for the perpetrator and the provision of restitution or compensation for victims.